On combining F0 contour and Vocal tract length normalisation for speech recognition of Vietnamese proper names - Huy, Ngô Hoàng (Journal of Computer Science and Cybernetics, 2012)
This paper presents a study and experiment on combination effect of F0 feature and vocal tract length normalisation (VTLN) to improve the HMM-based continuous speech recognition system performance for proper Vietnamese name sets. Our experimental results on the recognizer, independent speaker with speech feature based on F0 contour and MFCC warped by VTLN, for an university name set that has high duplicaton of syllables and words, already well normalized frequency variation of new speakers and improved the recognition performance.